Measles and Rubella Immunity Profile of Healthcare Workers in Bulgaria: A Cross-Sectional Study - Stefka Krumova; Zhivka Getsova; Lora Veleva; Radostina Stefanova; Tencho Tenev; Elitsa Golkocheva-Markova (Vaccines, 2026)
Healthcare workers (HCWs) and medical providers are regularly exposed to a wide range of infectious diseases in the course of their duties. This occupational risk is significant in the context of highly contagious infections such as measles, which can spread rapidly in healthcare institutions. This study aimed to assess the seroprevalence of protective anti-measles and anti-rubella IgG antibodies and factors influencing immunity among HCWs across all 28 districts in Bulgaria. Methods: A total of 1854 individuals, including 540 (29%) doctors and 1314 (71%) medical specialists from all 28 districts in Bulgaria, were screened for protective immunity against measles and rubella. Serum samples were analyzed for the presence of protective IgG antibodies by ELISA (Enzyme-Linked Immunosorbent Assay) using commercial EUROIMMUN Anti-Measles/Anti-Rubella Virus IgG ELISA kits. According to the manufacturer’s instructions, the results were interpreted semi-quantitatively as positive, negative, and equivocal. Results: Anti-measles protective IgG antibodies were detected in 86.1% of participants for measles and in 95.2% for rubella. Our study found a statistically significant difference when analyzing demographic factors (age) for measles: the samples from older participants (over 50-year-old persons) were characterized by higher immunity levels; staff working in non-infectious-disease wards (n+ = 95.7%) were more frequently positive for rubella IgG antibodies compared to staff employed in infectious wards; and region locations varied for both groups. Gender and professional roles were not significant predictors. Conclusions: HCWs are at a greater risk of contracting infections than the general public because they have contact with sick patients or infectious material. Their vaccination or IgG immunity status must be strictly monitored, especially to limit the spread of nosocomial infections in hospital settings.